The consistent criteria of hypotheses - L. Aleksidze; M. Mumladze; Z. Zerakidze (Modern Stochastics: Theory and Applications, 2014)
In this paper we define the consistent criteria of hypotheses such as the probability of any kind of errors is zero for given criteria. We prove necessary and sufficient conditions for the existence of such criteria.